Relatório de Estágio Profissional - O Professor de Educação Física na Prática de Ensino - Marco Paulo Coimbra de Abreu (2013)
The Practicum Training meant the possibility of experiencing teaching practice in real context. The stage was held in the High School Basic Senhora da Hora integrated on a group of practicum consists of 4 preservice Physical-Education teacher under the continuous monitoring of the Cooperating Teacher from school, and Faculty Tutor. This professional report is organized into four chapters. In the first chapter referred to as "Personal Dimension" realize a brief characterization of the personal self and reflect on expectations about the Practicum Training. On this last point I refer to what I founded at the beginning of the school year. In the second chapter I proceed to the "Framework for Professional Practice", referring to the legal context and institutional of the Practicum. The school as an institution and contextualization of my Practicum's context is heldin this part. The third chapter "Realization of Professional Practice" is organized by the areas of performance contemplated in the Regulations and Standards Guiding Practicum Training: Area 1 - Organization and Management of Teaching and Learning, Area 2 e 3 - Participation in School and Relations Community and Area 4 - Professional Development, embodying the latter the role of reflection in my development. This chapter builds up on my experiences throughout the year Internship in which I tried to raise my formation as a teacher.